Musahars’ perspective on nature, culture and cosmology - Giri, Madhu (Journal of Nepalese Studies, 2024)
This paper tries to explore Musahars’ understanding and their behaviors about private property/possession, nature, and cosmology at large. Policymakers and change makers blamed that Musahars did not save private property, food, and money for their future. The establishment narrative in Madhes is, ‘Musahars are the destroyer of private property’. The community was essentialized as a metaphor for Banmanchhe (forest-human), an example of marginalization, and a sample of the illiterate community in Nepal. The main knowledge gap is, what is their understanding of private property, natural resources, and cosmology? How do they interpret themselves, other people, and nature? How do they interpret life, property, happiness, and death? To address such a series of questions, the researcher employed ethnographic observation, and key informant interviews during a fieldwork at Golbazar (Siraha, Nepal), in 2013-2017. Musahars have different understandings of life, private property, and cosmology. They believed that all natural resources were collective property including non-human by nature but powerful people exploited them by making rules of private property relations. Musahars’ cosmological and natural understanding is that they could communicate and understand natural entities (wild animals, soil, trees, water, and air) and cosmological phenomena (spirits, gods, souls) and vice-versa.